INFORMASI MANAJEMAN LABA SEBAGAI PENENTU HARGA SAHAM PADA PERUSAHAAN INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Indatul Mukarromah; Pujiono (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to evaluate earnings management agains market decision consideration. One of the factor that can influence investment decisions is the company’s stock value. The type of research used is a quantitative approach using secondary data. The object of this study is a company engaged in the infrastructure, utilities and transportation industries listed on the IDX. The data used comes from the company’s financial report data and stock price data. The results of this study indicate that there is a positive effect of earning management on stock prices, the researcher suggests that variables in the study can be added so that other factors that can influence stock prices and market decision can be identified